2021
DOI: 10.2147/jir.s329234
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization with MMP-7 in the Distal Colon is Crucial for Syndecan-2 Shedding in Dextran Sulfate Sodium-Induced Colitis Mice

Abstract: Introduction Syndecan-2 expression is elevated during chronic inflammation and cancer development, and its shedding is observed in cancer patients. However, it remained unknown whether inflammation triggers syndecan-2 shedding. Methods The colitis model was produced in C57BL/6 mice by oral administration of 2–3% dextran sulfate sodium (DSS) in the drinking water. Syndecan-2 and MMP-7 expression levels in tissues and cells were detected by real-time PCR, Western blotting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
0
1
Order By: Relevance
“…found a strong positive correlation between MMP-7 expression in the glandular epithelium and the location of the lesion in both UC and CD patients ( 34 ). It has also been reported that MMP-7 expression levels vary along the colon ( 36 ), which is supported by our IHC data also showing differential MMP-7 levels in different areas of the colon. However, the origin of MMP-7 in the inflamed colon has not been fully characterized, partly because MMP-7 is a secreted protein with a relatively short half-life.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…found a strong positive correlation between MMP-7 expression in the glandular epithelium and the location of the lesion in both UC and CD patients ( 34 ). It has also been reported that MMP-7 expression levels vary along the colon ( 36 ), which is supported by our IHC data also showing differential MMP-7 levels in different areas of the colon. However, the origin of MMP-7 in the inflamed colon has not been fully characterized, partly because MMP-7 is a secreted protein with a relatively short half-life.…”
Section: Discussionsupporting
confidence: 91%
“…It is worth noting that smooth muscle cells, the predominant cell type in the intestine, also express MMP-7 in response to IL-4 and IL-13, which might contribute to IBD complications like perforation or fistula. Surprisingly, IL-6, which was reported to have an important role in MMP-7 expression in colonocytes ( 36 , 40 ), had no effect on MMP-7 expression in our cells. Further research is required to address this discrepancy.…”
Section: Discussioncontrasting
confidence: 64%